The Structure and Function of the Pericellular Matrix of Articular Cartilage - Wilusz, Rebecca E. (2014)
Chondrocytes in articular cartilage are surrounded by a narrow pericellular matrix (PCM) that is both biochemically and biomechanically distinct from the extracellular matrix (ECM) of the tissue. While the PCM was first observed nearly a century ago, its role is still under investigation. In support of early hypotheses regarding its function, increasing evidence indicates that the PCM serves as a transducer of biochemical and biomechanical signals to the chondrocyte. Work over the past two decades has established that the PCM in adult tissue is defined biochemically by several molecular components, including type VI collagen and perlecan. On the other hand, the biomechanical properties of this structure have only recently been measured. Techniques such as micropipette aspiration, in situ imaging, computational modeling, and atomic force microscopy have determined that the PCM exhibits distinct mechanical properties as compared to the ECM, and that these properties are influenced by specific PCM components as well as disease state. Importantly, the unique relationships among the mechanical properties of the chondrocyte, PCM, and ECM in different zones of cartilage suggest that this region significantly influences the stress-strain environment of the chondrocyte. In this review, we discuss recent advances in the measurement of PCM mechanical properties and structure that further increase our understanding of PCM function. Taken together, these studies suggest that the PCM plays a critical role in controlling the mechanical environment and mechanobiology of cells in cartilage and other cartilaginous tissues, such as the meniscus or intervertebral disc.